2006
DOI: 10.1007/s00520-006-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, tunneled, noncuffed central venous catheter in cancer patients (Vygon): safety, efficacy, and complications

Abstract: Vygon catheters do not seem to induce more early and late complications as compared with other more expensive devices, except for disadvantage of the high incidence rate of accidental losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…There is no firm existing evidence regarding protection from BSI or site infections with use of a cuff . In our cohort, infections were not increased in individuals with noncuffed TSB‐CVCs.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…There is no firm existing evidence regarding protection from BSI or site infections with use of a cuff . In our cohort, infections were not increased in individuals with noncuffed TSB‐CVCs.…”
Section: Discussioncontrasting
confidence: 52%
“…The presence of a cuff did not affect TSB‐CVC line failure outcomes in our study. Previously, the presence of a cuff in tunneled CVCs has been linked to less frequent accidental removal . Theoretically, the looping of the catheter should also be less common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonimplanted devices may have a higher rate of accidental loss [13], and this may be expected to be the case for noncuffed devices inserted into upper limb veins, such as those in the current study. However, we did not observe CVC dislodgement in any of the studied CVCs, and these findings are consistent with a large study of oncology patients where durability was demonstrated when a similar device and insertion site were used [17].…”
Section: Discussionmentioning
confidence: 88%
“…16 A retrospective study assessing the safety and effectiveness of long-term, tunnelled, non-cuffed CVCs reported a CVC-related thrombosis incidence of 4.3%, most of which happened in patients with haematological malignancies (10 cases vs 3 cases with solid tumours). 17 A recent retrospective study reported an incidence of PICC-related symptomatic thrombosis of 0.15 per 1000 PICC-days. 18 Older studies have described that intraluminal thrombosis requiring catheter removal can occur at a frequency of 0.6-0.81 events per 1000 catheter-days.…”
Section: Retrospective Studiesmentioning
confidence: 99%